Teaching-learning model: the case of ICT in improving academic performance - Condor Tinoco, Enrique Edgardo (2019)
Explanatory hypothetical explanatory study, with a quasi-experimental design, whose objective was to demonstrate, how the teaching-cooperative learning model using ICT contributes to improve the level of academic performance in the contents: conceptual, procedural and attitudinal of the students of the School Systems Engineering Professional of the José María Arguedas National University (UNAJMA) The model indicated was developed according to the cooperative learning methodology proposed by the brothers Johnson, D., Johnson, R., y Holubec, E. (1999) and the development of the web platform based on a blog, forum, chat and a wiki, ICT tools. In the post-test analysis, the level of academic performance of the experimental group has improved, since the students obtained averages within the categories of the high and medium academic performance level with 50.00% and 25.00% respectively, while in the control group concentrated the level of medium and low academic performance with 58.33% and 33.33% respectively. Significant differences were found in the level of academic performance of the control and experimental group in the post-test.